1993
DOI: 10.1007/bf00299336
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of serum concentration of squamous cell carcinoma antigen in anal epidermoid carcinoma

Abstract: The prognostic significance of pre-treatment serum concentration of squamous cell carcinoma antigen (SCCAg) was investigated in a population of 60 patients with anal epidermoid cancer. Serum concentration was determined during the period 1985-90. The patients were followed until December 1991. An antigen level above 2.0 ng/ml was classified as elevated. Thirty-eight patients had T1-2 tumours, while 22 had T3-4 tumours. Sixteen of the 20 patients (80%) with an elevated SCCAg concentration relapsed or had residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…For DSS, the rates were 83% versus 45%, respectively (P 5 .004). 20 The current study documents levels of SCCAg before the receipt of definitive treatment in a cohort of patients who were treated in a very similar fashion, whereas other reports have included a mixture of patients with primary and recurrent disease, including metastases. 19 In patients with cervical carcinoma, more advanced tumor classifications are associated with higher levels of serum SCCAg.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For DSS, the rates were 83% versus 45%, respectively (P 5 .004). 20 The current study documents levels of SCCAg before the receipt of definitive treatment in a cohort of patients who were treated in a very similar fashion, whereas other reports have included a mixture of patients with primary and recurrent disease, including metastases. 19 In patients with cervical carcinoma, more advanced tumor classifications are associated with higher levels of serum SCCAg.…”
Section: Discussionmentioning
confidence: 91%
“…For these reasons, SCCAg is a useful tumor marker in cervical cancer, but its utility as a tumor marker for SCCACM has been less thoroughly investigated. [17][18][19][20] In our department, pretreatment SCCAg measurement by 1 of the 4 treating radiation oncologists (R.G.-J.) has been part of routine initial diagnostic workup before CRT in SCCACM since 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, three studies failed to meet the inclusion criteria, as the primary form of treatment in these studies was radical surgery rather than chemoradiation. Ultimately, 21 studies remained for full inclusion in this literature review (Figure 1) (Fontana et al , 1991; Tanum et al , 1992; Goldman et al , 1993; Holm and Tanum, 1996; Tanum and Holm, 1996; Allal et al , 1998, 2003, 2004; Grabenbauer et al , 1998; Bonin et al , 1999; Indinnimeo et al , 1999, 2000a, 2000b, 2001; Wong et al , 1999; Holm et al , 2001; Le et al , 2005; Alvarez et al , 2006; Nilsson et al , 2006; Bruland et al , 2008; Ajani et al , 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Goldman et al (1993) examined the prognostic significance of this tumour marker and reported a clear association between SCCAg levels and survival (Table 8). Higher pretreatment serum SCCAg levels correlated with reduced tumour-free survival ( P <0.00005) and overall survival ( P =0.02) using multivariate analysis (Goldman et al , 1993).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation